Targeting BTK with Ibrutinib in Relapsed Chronic Lymphocytic Leukemia - Byrd, John C. (2013)
BACKGROUND: The treatment of relapsed chronic lymphocytic leukemia (CLL) has resulted in few durable remissions. Bruton's tyrosine kinase (BTK), an essential component of B-cell–receptor signaling, mediates interactions with the tumor microenvironment and promotes the survival and proliferation of CLL cells. METHODS: We conducted a phase 1b–2 multicenter study to assess the safety, efficacy, pharmacokinetics, and pharmacodynamics of ibrutinib (PCI-32765), a first-in-class, oral covalent inhibitor of BTK designed for treatment of B-cell cancers, in patients with relapsed or refractory CLL or small lymphocytic lymphoma. A total of 85 patients, the majority of whom were considered to have high-risk disease, received ibrutinib orally once daily; 51 received 420 mg, and 34 received 840 mg. RESULTS: Toxic effects were predominantly grade 1 or 2 and included transient diarrhea, fatigue, and upper respiratory tract infection; thus, patients could receive extended treatment with minimal hematologic toxic effects. The overall response rate was the same in the group that received 420 mg and the group that received 840 mg (71%), and an additional 20% and 15% of patients in the respective groups had a partial response with lymphocytosis. The response was independent of clinical and genomic risk factors present before treatment, including advanced-stage disease, the number of previous therapies, and the 17p13.1 deletion. At 26 months, the estimated progression-free survival rate was 75% and the rate of overall survival was 83%. CONCLUSIONS: Ibrutinib was associated with a high frequency of durable remissions in patients with relapsed or refractory CLL and small lymphocytic lymphoma, including patients with high-risk genetic lesions. (Funded by Pharmacyclics and others; ClinicalTrials.gov number, NCT01105247.)